Neuere Versuche der Bestimmung der Primärproduktion der Wälder und forstlicher Ertragspotentiale - Windhorst, Hans-Wilhelm (ERDKUNDE, 1979)
The paper shows that the results of the International Biological Program concerning the primary productivity of the biosphere have not found appropriate acknowledgement so far in geographical research. The author demonstrates that it is necessary to get a better insight into these problems not only for exact estimations of the possibilities of wood production in the specific forest formations but also for securing the food supplies especially in the developing countries. After explaining the various methods of measuring the primary productivity, several models of biologists, silviculturists, and geographers are compared. It is shown that it is almost impossible to compare these models in detail, as they are constructed from different points of view and are based on different schemes for distinguishing forest formations. Nevertheless an attempt is made to develop a new model estimating the potential productivity of the forests of the earth. From this synopsis it can be seen that the production potential of the tropical rain forest is often over-estimated. This is especially dangerous because of the specific ecological situation of the humid tropics. If the developed countries do not bring in their knowledge in using these forests without destroying the ecosystem, far reaching ecological as well as economic problems have to be expected. Selective exploitation as it is practiced now will have the effect that by the year 2000 no more primary forests in the tropics will be available for timber production.